The Rickettsia conorii Adr1 Interacts with the C-Terminus of Human Vitronectin in a Salt-Sensitive Manner - Fish, Abigail I.; Riley, Sean P.; Singh, Birendra; Riesbeck, Kristian; Martinez, Juan J. (Frontiers in Cellular and Infection Microbiology, 2017)
Spotted fever group Rickettsia species are inoculated into the mammalian bloodstream by hematophagous arthropods. Once in the bloodstream and during dissemination, the survival of these pathogens is dependent upon the ability of these bacteria to evade serum-borne host defenses until a proper cellular host is reached. Rickettsia conorii expresses an outer membrane protein, Adr1, which binds the complement inhibitory protein vitronectin to promote resistance to the anti-bacterial effects of the terminal complement complex. Adr1 is predicted to consist of 8 transmembrane beta sheets that form a membrane-spanning barrel with 4 peptide loops exposed to the extracellular environment. We previously demonstrated that Adr1 derivatives containing either loop 3 or 4 are sufficient to bind Vn and mediate resistance to serum killing when expressed at the outer-membrane of E. coli.By expressing R. conorii Adr1 on the surface of non-pathogenic E. coli, we demonstrate that the interaction between Adr1 and vitronectin is salt-sensitive and cannot be interrupted by addition of heparin. Additionally, we utilized vitroenctin-derived peptides to map the minimal Adr1/vitronectin interaction to the C-terminal region of vitronectin. Furthermore, we demonstrate that specific charged amino acid residues located within loops 3 and 4 of Adr1 are critical for mediating resistance to complement-mediated killing. Interestingly, Adr1 mutants that were no longer sufficient to mediate resistance to serum killing still retained the ability to bind to Vn, suggesting that Adr1-Vn interactions responsible for resistance to serum killing are more complex than originally hypothesized. In summary, elucidation of the mechanisms governing Adr1-Vn binding will be useful to specifically target this protein-protein interaction for therapeutic intervention